Does a rat free a trapped rat due to empathy or for sociality?. Issue 2 (25th July 2018) - Hachiga, Yosuke; Schwartz, Lindsay P.; Silberberg, Alan; Kearns, David N.; Gomez, Maria; Slotnick, Burton
Abstract : This report evaluates whether a rat releasing a trapped rat from a restraint tube is better explained as due to its empathic motivation or to the pursuit of social contact. In the first condition, each of six rats chose in an E maze between entering an empty goal box versus entering a goal box where its entrance caused a rat trapped in a restraint tube to be released. Rats preferred the goal box with the trapped rat over the empty goal box. In the second condition, these rats chose between releasing a restraint‐tube‐trapped rat in one goal box and another rat in the second goal box that was not locked into its restraint tube. Rats showed no preference between alternatives. In the third condition, rats chose between a goal box containing a rat with an open restraint tube and an empty goal box. Rats preferred the rat with the open restraint tube over the empty goal box. These results support attributing the response of releasing a rat from a restraint tube to the reinforcing power of social contact rather than interpreting this response as empathically motivated.